è¥¿åŠ å¤ç”¸ST. FRANSISKUS ASISI é«˜ä¸çš„æ±‰è¯æ•™å¦çŽ°çŠ¶åˆ†æž - Fadhilah, Endang Ulfa; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSt. Farnsiskus ASISI Senior high school is the one of private school which has Mandarin subject, in St. Farnsiskus ASISISenior high there is a difference, not only Tionghoa student but also non Tionghoa students, such as dayaknees and the other ethnics, so that the student response in learning Mandarin is also different.In order to know and understand about the condition of the teaching process in Senior high school St. Fransiskus Asisi, the writer interviewed the headmaster and collected the information through questioner from teachers and students. The result shows that the problems are mostly come from the students? factors, which is 30.30% of the students dislike Mandarin subject, 52% of the students have the difficulty on pronounciation and Hanzi writting, and only 15.2% of the students think that the teaching method used at school is not suitable with them.Key words: learning Mandarin, learning condition, teaching factor